Deaths and complications associated with the management of acute immune thrombotic thrombocytopenic purpura. Issue 4 (21st February 2020) - Colling, Meaghan; Sun, Lova; Upadhyay, Vivek; Ryu, Justine; Li, Ang; Uhl, Lynne; Kaufman, Richard M.; Stowell, Christopher P.; Dzik, Walter H.; Makar, Robert S.; Bendapudi, Pavan K.
Abstract : BACKGROUND: The introduction of therapeutic plasma exchange (TPE) dramatically decreased mortality in patients with immune thrombotic thrombocytopenic purpura (iTTP). However, there are few modern descriptions of residual causes of death from iTTP and complications associated with TPE. STUDY DESIGN AND METHODS: This was a retrospective study in a multi‐institutional cohort of 109 patients with iTTP between 2004 and 2017. Complications of TPE were analyzed in a subset of this cohort (74 patients representing 101 treatment courses). RESULTS: Death occurred in 8 of 109 patients (7.3%) and in 8 of 219 captured episodes of acute iTTP (mortality rate per episode: 3.7%). Neither the number of TPE treatments nor length of hospitalization predicted mortality. The majority of deaths (5/8) were associated with delay in the diagnosis of iTTP or initiation of TPE or presentation to the hospital in a moribund state. A subset of patients (N = 74) was analyzed for TPE‐related complications. Most patients (56/74; 76%) had at least one minor or major complication of TPE. Seven of 101 (6.9%) discrete treatment courses were associated with one or more severe complications, including anaphylaxis and line‐associated infections and thrombosis. Overall, the most frequent adverse events were mild allergic (urticarial) transfusion reactions, which affected 34 of 101 (34%) treatment courses. One patient died from a TPE‐related complication, line‐associated bacteremia. CONCLUSION: Early identification of patients with iTTP and the rapid initiation of TPE are paramount in preventing mortality. While TPE was associated with a high rate of adverse events, the vast majority were treatable and TPE‐related mortality is low.